2020
DOI: 10.7717/peerj.9644
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome dynamics in the tissue and mucus of acroporid corals differ in relation to host and environmental parameters

Abstract: Corals are associated with diverse microbial assemblages; however, the spatial-temporal dynamics of intra-species microbial interactions are poorly understood. The coral-associated microbial community varies substantially between tissue and mucus microhabitats; however, the factors controlling the occurrence, abundance, and distribution of microbial taxa over time have rarely been explored for different coral compartments simultaneously. Here, we test (1) differentiation in microbiome diversity and composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 94 publications
(138 reference statements)
3
37
0
Order By: Relevance
“…However, a similarly high abundance of Cyanobacteria was not previously observed in P. acuta from Raffles. The high abundance of Cyanobacteria found in corals from Raffles in this study could be linked to the elevated nitrate concentrations observed there, as Cyanobacteria can process nitrate and has been positively correlated with nitrate concentrations [39]. Elevated Cyanobacteria abundance has been associated with coral reef ecosystem degradation, and some Cyanobacteria can be a precursor to coral disease [40,41].…”
Section: Discussionmentioning
confidence: 58%
“…However, a similarly high abundance of Cyanobacteria was not previously observed in P. acuta from Raffles. The high abundance of Cyanobacteria found in corals from Raffles in this study could be linked to the elevated nitrate concentrations observed there, as Cyanobacteria can process nitrate and has been positively correlated with nitrate concentrations [39]. Elevated Cyanobacteria abundance has been associated with coral reef ecosystem degradation, and some Cyanobacteria can be a precursor to coral disease [40,41].…”
Section: Discussionmentioning
confidence: 58%
“…Aside from nutrient cycling and primary productivity in the ocean, marine microbes carry vital functions in host physiology. Microbiomes of several important benthic species have been studied to understand their community structure and function and how they relate to the surrounding environment's microbial pool (Barott et al, 2011;Ainsworth et al, 2015;Campbell et al, 2015;Jensen et al, 2019;Ziegler et al, 2019;Marchioro et al, 2020). Holobionts present a variable microbiome which differs across distinct individuals of the same species, and a core microbiome which is defined as a group of persistent microbes across all individuals of the same species, for which we can infer a potentially vital role in the holobiont (Hernandez-Agreda et al, 2017;Pita et al, 2018).…”
Section: Marine Microbiomesmentioning
confidence: 99%
“…Host-associated microbiomes tend to present a clear distinct community composition from the surrounding environment (Barott et al, 2011;Jensen et al, 2019;Marchioro et al, 2020). It was demonstrated that deep-sea corals host highly specific bacterial communities with the most abundant OTUs (operational taxonomic units) only accounting for <0.1% of the surrounding seawater bacterial community (Jensen et al, 2019).…”
Section: Marine Microbiomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Synechococcus is a photoautotrophic cyanobacterium found in surface waters harbouring abundant light. Both corals and their symbiotic algae are known to actively feed on Synechococcus (Jeong et al 2012;McNally et al 2017) which is often found as a member of the coral surface mucus microbiome (Marchioro et al 2020). As a food for corals, it has been suggested that nitrogen-rich Synechococcus cells may increase bleaching recovery and coral health (Meunier et al 2019).…”
Section: Microbiome Communities Vary Across Depths and Are Enriched In Shallow Habitatsmentioning
confidence: 99%